Transformasi Pembelajaran di Era Digital: Penerapan Media Pembelajaran Interaktif untuk Meningkatkan Keterampilan Guru SMP di Kabupaten Takalar - Fhatiah Adiba; Andayani, Dyah Darma; Andi Akram Nur Risal; Edy, Marwan Ramdhany; Surianto, Dewi Fatmarani (Jurusan Teknik Informatika dan Komputer, 2023)
This community service activities aims to evaluate the impact of instructional media training on participants' preferences and understanding, with a focus on the use of Canva as an alternative to PowerPoint. The pre-test indicated that the majority of participants had little or no experience using Canva before the training, while PowerPoint was a commonly used tool. After the training, there was a significant increase in participants' preferences and understanding of Canva, with 51.7% preferring it. Although 41.4% of participants found Canva easier to use, some still maintained a preference for PowerPoint (31%). Supportive factors for the success of these changes included well-organized and professional training, clear content, interactive teaching methods, guidance, and hands-on practice. However, old habits and initial discomfort with new platforms served as inhibiting factors. The outreach team is optimistic that with continued support and more practice, participants will become more comfortable and proficient in using interactive learning media. In conclusion, these changes in preferences and understanding are expected to become more consistent and supportive of increased use of interactive learning media in the learning context.